Serving on WeChat: understanding the logics of police’s engagement with the public in Chinese contexts - Liu, Tzu-Hsuan (International journal of law, crime and justice, 2024)
This study investigated how Chinese police engage with the public via WeChat to manage their image, communicate risks, and enhance legitimacy. Drawing on supervised machine learning and topic modeling of 162,981 posts by 31 provincial capital Chinese police forces on WeChat from 2013 to 2020, this study categorized three periods, encompassing six types of posts: image building, civil service, political broadcasting, crime broadcasting, crime prevention advocacy, and others. The results demonstrated a significant decline in image management posts during the pandemic, as the police prioritized risk communication. The research also highlights the increased use of political broadcasting posts during crucial political events. Furthermore, image management posts constitute a substantial portion of image-building content, while civil service posts increasingly emphasize risk communication, especially during the pandemic. In conclusion, the study provides valuable insights into the evolving presentation strategies of Chinese police on WeChat, revealing their multifaceted use of social media.